Conservation, Markets & the Environment in Southern and Eastern Africa Commodifying the 'Wild' - Bollig, Michael; Mosimane, Alfons Wabahe; Nghitevelekwa, Romie Vonkie (Future Rural Africa, 2023)
Focuses on a much discussed and controversial aspect of conservation: the commodification of nature. Can the successful marketization of what is generally perceived as wilderness help to provide for biodiversity conservation, economic development and social emancipation? At a time of profound anxiety about the impact of human activity on nature and the catastrophic effects of climate change, the "sixth mass extinction", invasive species and rapidly expanding zoonotic diseases, this volume engages with the practices, discourses, and materialities surrounding the commodification of "the wild". Focusing on the relationship between commodification and wilderness, the contributors pay particular attention to commodification's newer iterations in which human management plays a significant role, such as wildlife-park tourism, trophy-hunting, and trade in herbal medicines, perfumes and luxury exotic food items. Dominant neoliberal approaches have aimed to address global environmental challenges through the commodification and marketization of nature: by valorizing nature, they claim, biodiversity can be safeguarded and "wild" landscapes protected. This, it is thought, will not only open up a new frontier of sustainable, non-exploitative, participatory capitalist expansion, but invigorate rural livelihoods, reduce poverty, and add important assets to otherwise vulnerable rural economies. This important book challenges this future trajectory. Investigating a broad range of cases across southern and eastern Africa, from the illegal sandalwood trade to legal trade in devil's claw and honeybush, to trophy-hunting and wilderness safaris, the contributors reveal the pitfalls and challenges of commodification, what this means for the continent and beyond. OPEN ACCESS: This title is available under the Creative Commons license CC-BY-NC-ND